The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1540-5885.2011.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Encroachment Patterns of the “Best Products” from the Last Decade*

Abstract: Based on the examination of 239 ''best products'' (all those on Business Week's annual lists from the past decade), this article tests and validates a conceptual framework identifying six ways in which new products open new markets and/or encroach on original products. Three of these six scenarios involve high-end encroachment (the new product first opens a new high-end market, or enters at the high end of an existing market, and then diffuses down-market), and three scenarios involve low-end encroachment (enc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…In this school of thought, Utterback and Acee provided a more comprehensive view of technological innovations by adding the third dimension – ancillary performance – and what Christensen defined as disruptive innovation was one of the eight possibilities (Utterback and Acee 2005). Van Orden et al . (2008) further proposed a comprehensive framework including three high‐end and three low‐end encroachment patterns, and emphasized that the three high‐end encroachment patterns (with destructive effects) are not disruptive.…”
Section: Definition Of Disruptive Innovationmentioning
confidence: 99%
“…In this school of thought, Utterback and Acee provided a more comprehensive view of technological innovations by adding the third dimension – ancillary performance – and what Christensen defined as disruptive innovation was one of the eight possibilities (Utterback and Acee 2005). Van Orden et al . (2008) further proposed a comprehensive framework including three high‐end and three low‐end encroachment patterns, and emphasized that the three high‐end encroachment patterns (with destructive effects) are not disruptive.…”
Section: Definition Of Disruptive Innovationmentioning
confidence: 99%
“…This is due to the changing preferences of both core and ancillary attributes that constitute an attribute set upon which customers decide their purchase. More recently, it has been observed that core attributes still play a critical for the adoption of high-end successful products (Van Orden et al, 2011). Therefore, we propose, H3 Lowering the attributes of overshooting in reference to consumer preferences tends to decrease the adaptation of disruptive innovation products in the low-end market.…”
Section: Overshooting: Price Vs Performancementioning
confidence: 93%
“…It is not clear though, that all innovative products follow the previous pattern. Van Orden et al (2011) identify that a majority of innovations encroach directly to the high-end segment of the market but their prices are not inevitably high. Similarly, it has been suggested (Utterback and Acee, 2005) that products may also be high-performing, high-price innovations that compete in a mature market segment that eventually embraces the mass market.…”
Section: Emerging Driversmentioning
confidence: 99%
“…For example, the winners of IDSA's yearly IDEA competition could represent an expertly selected sample of “great” design that could be analyzed in various ways, potentially resulting in publishable articles. For an example of an analogous piece of research in the NPD field which analyzes Business Week 's “Best Products” as a data set, see van Orden, Van der Rhee, and Schmidt (2011).…”
Section: Partner With a Professional Associationmentioning
confidence: 99%